PRE-SERVICE TEACHERS’ PERSPERCTIVE ABOUT USING GOOGLE TRANSLATE IN VOCABULARY BUILDING - Bayuaji , Abdilah Rajib; Febriansyah, Salman; Saputra, Dimas Abimanyu; Wijirahayu , Suciana (UICELL, 2023)
This study aims to investigate the extent to which Indonesian students rely on Google Translate (GT) as a tool for learning English. The benefits of using Google Translate in students are to develop their vocabulary. The research approach used surveys for researcher-participant interaction. The participants used in this research are purpose participants who refer to 36 third-semester students of English education. We used qualitative research methods, which involved a questionnaire as an instrument. The preliminary study results prove that some students still use Google Translate to find new vocabulary. This research will open up new perspectives on digital tools for vocabulary building. Keywords: Pre-Service Teachers, Google Translate, Vocabulary Building, EFL Student